Documentation of the pathological manifestations of the Portico of the Cultural Baptism of Goiânia - Art Déco historical monument - Lara Pio Santos, Taís; Silva Júnior, Paulo Francinete (Revista ALCONPAT, 2021)
This article aims to present the methodology for the inspection and mapping of pathological manifestations of the Portico of Cultural Baptism of Goiânia. It is a monument from the beginning of the 1940s, representative of the Art Deco architectural style. In 2003 this monument was listed by the National Historical and Artistic Heritage Institute, but despite its invaluable historical importance, the structure has several pathological manifestations. To achieve this objective, the following procedures were performed: (1) visual inspection; (2) photographic record; (3) anamnesis and (4) trials. The tests performed were sclerometer, cover meter, and strain measurement. The main pathological manifestations identified were cracking, mortar detachment, reinforcement corrosion and excessive deformation.